Determination of the effect of fabric properties on the coupled heat and moisture transport of underwear–shirt fabric combinations. Issue 11 (June 2018) - Atasağun, Hande G; Okur, Ayşe; Psikuta, Agnes; Rossi, René M; Annaheim, Simon
In this study, the heat transfer and moisture management properties of fabric combinations for office wear consisting of underwear and shirt fabrics, including three different fiber types and three kinds of weave types, were investigated. A sweating torso methodology was applied in order to characterize fabric combinations in terms of thermophysiological comfort for office occupants. This study showed that the cooling effect due to perspiration, accumulated moisture, and drying time of the combinations with cotton underwear were unaffected by both weave type and fiber type of shirt layer. However, initial cooling and drying time values of the combinations with underwear consisting of hydrophobic fibers were affected statistically significant by the fiber of the shirt layer. The percentage of moisture accumulation in the fabric layers was directly related to the fiber type of the underwear fabrics. Based on an extended data analysis, it was concluded that the combination of polyester underwear and cotton polyester twill shirt fabrics was the most recommendable of all the combinations used in this study with regard to the thermophysiological comfort of office occupants.